Pendekatan Empati dalam Manajemen Krisis Maskapai: Studi pada Batik Air - Ramadhani, Alya; Ayuningtyas, Fitria (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The incident involving a pilot falling asleep on duty with Batik Air highlights the importance of empathetic and transparent crisis communication in maintaining a company's reputation and public trust. This study aims to analyze the role of emotional approaches in crisis communication and how empathy-driven communication strategies can be used to restore public trust and protect the company's reputation. The research employs a qualitative method with a case study approach, analyzing data from media reports, official company statements, and relevant crisis communication literature. The findings indicate that communication sensitive to public emotions, including acknowledgment of mistakes, a sincere apology, and the communication of corrective action plans, can significantly ease emotional tensions and enhance customer trust. This study underscores the importance of building emotional connections with the audience through empathy-oriented communication strategies. On the other hand, Batik Air's defensive approach, while based on risk considerations, was not fully effective in alleviating the crisis. The study concludes that a sincere apology and acknowledgment of mistakes are more effective in rebuilding public trust and improving the company's image. The theoretical implications of these findings emphasize the need for integrating both technical and emotional elements in crisis communication strategies, highlighting the necessity for companies to prioritize empathy in their responses to crises.